EFL Students’ Perceptions and Challenges in Using Paperpal as an AI Feedback Tool for Research Paper Writing - Hilyati Fitria Harahap; Rahmah Fithriani; Utami Dewi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates undergraduate EFL students’ perceptions and challenges in using Paperpal as an AI feedback tool for research paper writing. Although AI-assisted writing tools are increasingly integrated into higher education, empirical research examining students’ experiences with AI-generated feedback in research-oriented writing remains limited, particularly in EFL contexts. Employing a qualitative case study design, this study involved 25 undergraduate English Education students at a state university in Indonesia. Data were collected through a descriptive questionnaire administered to all participants and semi-structured interviews with 10 selected students. Questionnaire data were analyzed using Likert-scale frequency analysis, while interview data were examined through thematic analysis. The findings indicate that students generally perceived Paperpal as a useful and accessible tool that supported grammatical accuracy, sentence clarity, academic vocabulary development, revision efficiency, and confidence during the research paper revision process. However, the study also reveals notable challenges. Students reported difficulty maintaining intended meaning and authorial control when applying AI-generated feedback, particularly in complex argumentative sections. In addition, a tendency toward over-reliance on AI feedback was identified, especially among less confident writers, which occasionally reduced critical evaluation of revisions. Overall, the study concludes that Paperpal functions most effectively as a complementary linguistic support rather than a standalone solution. Its pedagogical value depends on students’ feedback literacy and their ability to engage critically with AI-generated feedback, underscoring the need for guided and responsible integration of AI tools in EFL academic writing instruction.